EVALUACIÓN DE LA ESTRUCTURA ESTRATÉGICA EN LAS PYMES DEL SECTOR METALMECÁNICO EN EL DISTRITO DE LOS OLIVOS 2019-2021 - ORTEGA ZAVALA, Daniel L. (2022)
“This publication describes the situation of micro and small companies (pymes) in the metalworking sector in the Los Olivos district. Currently there are various studies on the situation of pymes and they argue the importance of the development and growth of these companies at the business level to improve the performance of your organization. According to the study carried out at the demographic, economic, social, educational level; the reality in which they carry out their activities was known. 62% of the current population is made up of young people and adults. Households have access to means of communication such as television, internet and telephony. Pymes carry out activities under artisanal methods. The lack of financial support from the state or private entrepreneurs to carry out research & development (I&D) activities in the metalworking sector prevents them from innovating products and being more competitive. Based on the results, it was proposed to create an Association of Entrepreneurs of the Infantas Industrial Park in the Los Olivos district (AMPEI), a steering committee and statutes; develop training programs; find entities that finance pymes with competitive interest rates.“